2018
DOI: 10.1007/s13593-018-0513-7
|View full text |Cite
|
Sign up to set email alerts
|

Vine and citrus mealybug pest control based on synthetic chemicals. A review

Abstract: Synthetic chemicals are extensively used to limit the substantial crop damage induced by two closely related scale insects, the vine mealybug Planococcus ficus (Signoret) and the citrus mealybug Planococcus citri Risso (Hemiptera: Pseudococcidae). Both organisms are economically important pests occurring in vineyards and/or in citrus orchards worldwide. Synthetic chemicals can be either incorporated in pesticides aimed at directly controlling these pests or used as semiochemicals (i.e., sex pheromones) for mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 133 publications
(190 reference statements)
0
48
0
Order By: Relevance
“…ficus below damaging levels. Historically, the pesticides applied included chlorinated hydrocarbons (e.g., DDT) and organophosphates (e.g., parathion), but these have largely been replaced by newer materials with different modes of action, such as neonicotinoids, insect growth regulators, botanicals, and biosynthesis inhibitors [ 26 , 27 , 28 , 29 ]. For organic or sustainable farming programs, neem, light mineral oils, lime-sulfur, citrus products, and fatty acid soaps have been used.…”
Section: Introductionmentioning
confidence: 99%
“…ficus below damaging levels. Historically, the pesticides applied included chlorinated hydrocarbons (e.g., DDT) and organophosphates (e.g., parathion), but these have largely been replaced by newer materials with different modes of action, such as neonicotinoids, insect growth regulators, botanicals, and biosynthesis inhibitors [ 26 , 27 , 28 , 29 ]. For organic or sustainable farming programs, neem, light mineral oils, lime-sulfur, citrus products, and fatty acid soaps have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Planococcus ficus is a serious insect pest of grapes with no management tools that provide complete control [14,20,23,[49][50][51][52]. We evaluated 10 grape cultivars, rootstocks, and species for their relative resistance to P. ficus population growth in field-based cage studies.…”
Section: Discussionmentioning
confidence: 99%
“…Planococcus ficus (Signoret) is one of the most important vineyard mealybugs that has a global distribution [14], is a known vector of GLRaVs [15][16][17][18], and has become the primary pest in California vineyards [19]. Integrated pest management (IPM) systems are integral for mealybug management primarily in the table and wine grape markets, and include cultural practices, such as cluster thinning and bark stripping; however, most farmers still rely on chemical controls to minimize exposure of the clusters to mealybugs [19,20]. More sustainable tools for P. ficus control include mating disruption, which is currently being used or tested worldwide as an alternative or complement to insecticide sprays [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Another potential control system of this pest could be MD. Indeed, the latter has been found effective for the management of the vine mealybug, P. ficus [16,20,21,22,36,37]. Earlier tests revealed that habituation to the sex pheromone did not occur in P. calceolariae [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, to boost grape production under an environmentally-safe agricultural system, it is necessary to find alternative solutions to effectively manage crop pests while reducing insecticide overuse [12,13,14]. Hence, it is critical to develop more sustainable Integrated Pest Management (IPM) systems [15,16]. An alternative is presented in synthetic sex pheromones, which disrupt the chemical communication between male and female of a given insect species, thereby preventing mate location and mating [17].…”
Section: Introductionmentioning
confidence: 99%